2022
DOI: 10.1108/bfj-09-2021-1051
|View full text |Cite
|
Sign up to set email alerts
|

Substituting meat and the role of a situational context: exploring associations and motives of Dutch meat substitute-users

Abstract: PurposeThe Dutch market for meat substitutes has grown steadily, however, their market share is still low, and meat consumption in the Netherlands is not decreasing. For a transition towards a more plant-based diet, understanding consumer motives regarding meat substitutes is important. The purpose of this study was to explore what motives lay behind the appropriateness of the use of meat substitutes in different usage situations.Design/methodology/approachIn total, 20 semi-structured in-depth interviews were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…Apparently, the main reasons for this shift in consumers' approach to the meat consumption relies on the growing attention given to the impact of such behaviours over the environment, health and the so-called “animal welfare” (i.e. the avoidance of intensive animal farming) (Elzerman et al ., 2022). Thus, more research in this trajectory is needed.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Apparently, the main reasons for this shift in consumers' approach to the meat consumption relies on the growing attention given to the impact of such behaviours over the environment, health and the so-called “animal welfare” (i.e. the avoidance of intensive animal farming) (Elzerman et al ., 2022). Thus, more research in this trajectory is needed.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…On the other hand, other research revealed a lack of awareness of the mental association between meat consumption and climate change ( 44 ). In depth interviews with 20 Dutch consumers revealed mainly positive or neutral mental associations with meat substitutes, such as “traditional meat replacement,” “nutrition substitution” or “specific meat substitute products” ( 45 ). Interestingly, there was no consensus on the requirements for meat substitute products, some respondents indicated that meat substitute products should be similar to real meat while others held the opposite opinion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interestingly, there was no consensus on the requirements for meat substitute products, some respondents indicated that meat substitute products should be similar to real meat while others held the opposite opinion. It needs to be mentioned that all of the 20 respondents were familiar with meat substitute products and some of them were vegetarian ( 45 ). However, other studies acknowledged the challenge to attract not only vegetarians but people who regularly eat meat ( 16 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the extrusion process, several factors are involved in the retention or loss of volatile compounds, including raw material composition and moisture content, extrusion conditions (residence time, extruder temperature, compression and pressure, vapor loss during expansion, and diffusivity of the volatiles in the mass). Elzerman et al [ 56 ] reported that PBM products that mimic the sensory characteristics of meat may appeal to consumers who frequently consume meat. However, when sensory characteristics do not meet consumer expectations, even products with health benefits may be rejected by customers [ 85 ].…”
Section: Pbm Pleasure Drivers and Factors Involved In Product Successmentioning
confidence: 99%
“…Negative perceptions are more frequent in people who have not tried PBM products or who like animal meat and do not want to reduce their meat intake at any cost [ 54 , 55 ]. Elzerman et al [ 56 ] suggested that not everyone needs to go vegetarian but that reducing intake of meat a few days a week could help transition towards PBM and possibly lessen health-related issues associated with higher meat consumption.…”
Section: Introductionmentioning
confidence: 99%